Lifetime model adjustments for GaN cascodes as a base for inverter lifetime estimation - Florian Lippold; Regine Mallwitz (Power Electronic Devices and Components, 2023)
Lifetime models for GaN power semiconductors are essential for a reliable and long-term stable design of complete power electronics systems. Load power cycling investigates the connections between the semiconductor chip, the package and the system. In this paper, various GaN cascodes in TO-247 packages were cycled. The results were analyzed, so that empiric lifetime models could be derived. The aging of bond wires is mainly the cause for the end of life and therefore the Coffin-Manson-Approach can be used for the GaN lifetime modelling. The lifetime of an inverter equipped with this GaN devices is estimated and is assessed as being high.